Current State of Understanding of the Role of PACAP in the Hypothalamo-Hypophyseal Gonadotropin Functions of Mammals - Köves, Katalin; Szabó, Enikő; Kántor, Orsolya; Heinzlmann, Andrea; Szabó, Flóra; Csáki, Ágnes (Frontiers in Endocrinology, 2020)
PACAP was discovered 30 years ago in Arimura’s laboratory. During these three decades, it has become evident that this peptide plays a crucial role in mammalian organisms. Most important functions of PACAP are the following. 1. neurotransmitter, 2. neuromodulator, 3. hypophysiotropic hormone, 4. neuroprotector. It has an important role at all the three levels of the reproductive system. The paper overviews the data concerning the distribution of PACAP and its receptors in mammalian hypothalamus and pituitary, the role of PACAP in the gonadotropic hormone secretion of females and males, the interaction between PACAP, GnRH and sexual steroids and other hypothalamic peptides including the kisspeptin, and how PACAP may be involved in the reproductive functions through the biological clock. Finally, the place of PACAP in the hypothalamo-hypophysial system is discussed and the facts missing are highlighted that would help better understand the function of PACAP in this system.